Appe mango: pickling the cultural and biological diversity of Uttara Kannada district in the Western Ghats - Sthapit, B.; Vasudeva, R. (2011)
Uttara Kannada, one of the forest-rich districts of Karnataka, is well known for its biological diversity, rich cultural heritage and high level of awareness among its people on issues related to conservation. This flyer tells the story of Appe Mango and tackles questions such as, ‘What makes the people of Uttara Kannada tick for the conservation of biodiversity?’ and ‘How do they relate themselves to nature?’